NUTRITIVE SUPPORT OF YOUNG SPORTSMEN USING A SPECIALIZED RUSSIAN PRODUCT - T. E. Borovik; A. A. Baranov; S. G. Makarova; I. T. Korneyeva; S. D. Polyakov; T. R. Chumbadze (Union of pediatricians of Russia, 2013)
Organization of adequate nutrition of children and adolescents actively going in for sports is of the highest importance both for improving sports results and preserving children's health. On the modern stage of sports neutraceuticals development, it is relevant to substantiate approaches to nutrition on all stages of the training process, develop methodological basis for individual nutrition selection and conduct demonstrative trials in order to evaluate efficacy of nutritional measures. The pediatric nutrition department of the FSBI "Scientific Center of Children's Health" conducted a controlled trial of efficacy of a new Russian product for nutritive support of children in the training period in 2012 in order to study possibilities of nutrition optimization for young sportsmen. We noticed statistically significant alterations of bioimpedance analysis values - lean and active cell body mass - in the setting of nutrition correction - intake of 200-400 ml/day of the product for 21 days; at the same time, the fat mass remained the same. Psychological testing using WAN questionnaire (well-being, activity, mood) conducted in the recovery period of the training process also revealed positive dynamics. The product may be used in the dose of 200-400 ml at any time of day; at the same time, it is most reasonable to take it as an additional food intake in the event of considerable training stress immediately before or after training, when adequate nutrition organization is hindered.